Problematic Child Mealtime Behavior and Caregiver Mobile Phone Use. Issue 5 (June 2020) - Milkovich, Libby Matile; Sherman, Ashley; Dreyer Gillette, Meredith; Sweeney, Brooke; Nyp, Sarah; Black, Benjamin
ABSTRACT: Objective: To evaluate the associations of caregiver mobile phone problematic use and child problematic mealtime behaviors (PMBs) to improve understanding of the possible implications of caregiver mobile phone problematic use. Methods: Surveys were administered to caregivers of children aged 3 to 8 years. The survey included demographics, a validated measure for caregiver mobile phone problematic use (Mobile Phone Problematic Use Scale-10 [MPPUS-10]), and a validated measure for the perception of child PMB (Meals in our Household [MIOH]). The bivariate associations between child and caregiver characteristics, mobile phone problematic use, and PMBs of children were analyzed. Partial correlations examined these relations while controlling for significant ( p ⩽ 0.05) covariates. Results: Eighty-four caregivers (mean age 32.6 years, 63% white, 21% ⩽ high school completion) participated. The correlation of MIOH problematic behavior total with MPPUS-10 was significant (r = 0.33, p ⩽ 0.01). Significantly correlated caregiver variables with MPPUS-10 included age (r = −0.25, p = 0.02) and female sex ( p = 0.01). No significant caregiver variables were noted for PMB. Child's age was significantly correlated with PMB (r = −0.27, p = 0.01). MPPUS-10 and PMB correlation remained significant when controlling for significant covariates. Conclusion: A positive correlation existed between MPPUS-10 and PMB. Understanding the potential association between caregiver mobile phone problematic use and child PMB strengthens the pediatricians' ability to counsel about the implications of caregiver mobile phone problematic use when discussing child PMB.